A New Approach to Tone in Luganda - Hyman, Larry M.; Katamba, Francis X. (Language, 1993)
Since McCawley 1970, the Luganda tone system has been well known for its property of allowing at most one High]to Low pitch drop per word. To account for this property, the underlying system has been analyzed both in terms of underlying accents of various kinds (e.g. diacritic) and in terms of underlying tone (e.g. H vs. 0). Most accentual proposals, however, fail to account for the fact that THREE marks are necessary to characterize the high to low 'melody': a mark for the first H mora, a mark for the place of the H-to-L drop, and a mark for the place of the last L mora. After evaluating previous accentual and tonal analyses, we present a new approach to tone in Luganda that integrates tone and accent in the following way: (i) Accent in Luganda consists of designating certain moras as metrically strong (and hence capable of attracting tone); (ii) Tone in Luganda consists of lexical and grammatical occurrences of underlying HL contours (or 'potential pitch drops'). This new analysis, which continues to recognize the importance of the H to L pitch drop, provides additional evidence for the coexistence of tone and accent, which may interact in complex ways in the same language
Keywords: Approach; Tone; Luganda